Application of game theory to software user interface evaluation. Issue 1 (1st January 2018) - Nwobi-Okoye, Chidozie C.; Okiy, Stanley
Abstract: The choice of a software userinterface is very strategic. Usability testing alone often does not determine the best software user interface. Secondly, economic considerations and the fact that software performance is a stochastic dynamic process (Markov process), are often neglected in user interface evaluations. Hence, evaluation tools that better capture the overall user experience, in addition to user interface economics and dynamics, should evaluate software user interfaces more effectively. The psychological concept of flow has been proposed as better metric for measuring software user experience. Hence, a good software interface design should have flow characteristics, a virtual strategy. The strategic nature of software user interface necessitates the need for the best tool for modeling the strategic interaction among competing software firms/user interfaces. The decision problem therefore, is how to develop an approporiate game theoretic model to assist software userinterface designers. In the light of these shortcommings, game theoretic model using markov chains and the flow theory concept was used to model and obtain optimal/equilibrium software user interface among competing firms/userinterfaces. The results of the study show that game theoretic analysis would be a very useful tool for software user interface evaluation.